Effect of relative displacement and normal contact load on fretting fatigue behaviour of ti6al4v alloy - Buciumeanu,M. (2008)
The main objective of this work is to study the fretting fatigue behaviour of Ti6Al4V in contact with a dissimilar mating material 34CrNiMo6 steel, using a sphere-on-plane configuration. There are a significant number of parameters that may affect fretting fatigue. Relative displacement amplitude and normal contact load are usually considered the most relevant ones. Thus, the role of relative displacement amplitude and normal load on fretting fatigue, life is presented. When the Ti6Al4V alloy is subjected to fretting fatigue the fatigue life drastically reduces as compared to the traditional plain fatigue case. In order to study this detrimental effect of fatigue life tests of both plain fatigue and fretting fatigue were carried out, highlighting the synergic effect between fatigue and fretting. Three different normal loads were used in the experiments. The relative displacement amplitude was changed by varying the tangential load. The fretting fatigue experiments were carried out in a fretting fatigue apparatus assembled on a servo hydraulic fatigue testing machine. In addition to the experimental work a nonlinear analysis using ABAQUS was carried out to determine the influence of the normal load on fretting fatigue behaviour. It was verified the strong dependence of fretting fatigue life on the two studied variables, namely the relative displacement amplitude and the normal contact load.